2014
DOI: 10.1111/jbg.12096
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA diversity of Anatolian indigenous domestic goats

Abstract: Anatolia has been an important region for civilizations and agricultural revolution as a major domestication centre for livestock species. Goats (Capra hircus) were among the earliest domesticated animals in this region. In this study, genetic diversity of Anatolian goat breeds was characterized by comparison of mitochondrial DNA hypervariable region 1. A total of 295 individuals, including 99 Anatolian Black goats, 96 Angora goats and 100 Kilis goats, were used. Haplogroup A was found to be the dominant haplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
4
7
0
Order By: Relevance
“…This weak structure was also evidenced by limited genetic differentiations (mean pairwise Fst = 0.0168). Our results were consistent with previous studies [6,38,42]. The traditional nomadic culture of Mongolia may have contributed to this weak geographical structure and limited genetic differentiations among MG populations.…”
Section: Population Structure and Expansionsupporting
confidence: 93%
See 3 more Smart Citations
“…This weak structure was also evidenced by limited genetic differentiations (mean pairwise Fst = 0.0168). Our results were consistent with previous studies [6,38,42]. The traditional nomadic culture of Mongolia may have contributed to this weak geographical structure and limited genetic differentiations among MG populations.…”
Section: Population Structure and Expansionsupporting
confidence: 93%
“…This highly polymorphic region (indeed, the complete D-loop) has been routinely used in previous studies that examined genetic diversity, phylogenetic relationships, and especially the maternal origin of most domesticated animals, including goats [14,[33][34][35][36][37]. Similar to previous results [17,38,39], goats from Mongolia investigated in this study showed high mtDNA diversity. The assessed overall Hd and Pi of MG were 0.997 and 0.0283, respectively ( Table 1).…”
Section: Genetic Diversitysupporting
confidence: 80%
See 2 more Smart Citations
“…In recent years, studies on characterizing genetic diversity in goat breeds from some different countries and regions have been conducted by researchers. Among the studies are such as in Chinese goat (Wang et al, 2008), Sardinian goat (Piras et al, 2012), Arabian goat (Al-Araimi et al, 2017), East Asian goat (Lin et al, 2013), Moroccan goat (Benjelloun et al, 2011), Egyptian goat (Othman & Mahfouz, 2016;Ahmed et al, 2017), African goat Githui et al, 2016;Awotunde et al, 2015;Royo et al, 2009), American goat (Amills et al, 2009), Anatolian goat (Akis et al, 2014), Pakistani goat (Naqvi et al, 2017), and genetic diversity information in animal farm has been reviewed recently by Groeneveld et al (2010).…”
Section: Introductionmentioning
confidence: 99%